2003
DOI: 10.1152/ajpcell.00158.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organ culture on arterial gene expression and hypoxic relaxation: role of the ryanodine receptor

Abstract: . Effects of organ culture on arterial gene expression and hypoxic relaxation: role of the ryanodine receptor. Am J Physiol Cell Physiol 284: C999-C1005, 2003. First published December 11, 2002 10.1152/ajpcell.00158.2002.-Organ culture specifically inhibits vasorelaxation to acute hypoxia and preferentially decreases specific voltage-dependent K ϩ channel expression over other K ϩ and Ca 2ϩ channel subtypes. To isolate further potential oxygen-sensing mechanisms correlated with altered gene expression, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…8A) is consistent with findings in other rat arterial smooth muscle preparations, including aorta, superior and inferior mesenteric (59), coronary (70), and main pulmonary arteries (80), but not basilar arteries (65). Our real-time PCR data, however, show that RyR2 is the most abundant transcript in rat cerebral artery myocytes, with RyR3 less highly expressed and RyR1 barely detected (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…8A) is consistent with findings in other rat arterial smooth muscle preparations, including aorta, superior and inferior mesenteric (59), coronary (70), and main pulmonary arteries (80), but not basilar arteries (65). Our real-time PCR data, however, show that RyR2 is the most abundant transcript in rat cerebral artery myocytes, with RyR3 less highly expressed and RyR1 barely detected (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with others' reports, our results showed that RyR-mediated Ca 2+ release is over-activated in hypoxic VSMCs, which might be owing to the increased expression of RyR and the increased sensitivity of RyR to Ca 2+ [25,26] . Furthermore, the over-activation of RyRmediated Ca 2+ release is closely associated with the occurrence of vascular hyporeactivity to NE in hemorrhagic shock rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, expression of multiple RyR subtypes is common in many other tissues. In rat aorta, mesenteric arteries, cerebral arteries, portal veins, and porcine coronary arteries, coexpression of all three RyR subtypes has been reported (6,32,35,49). Evidence suggests that RyR1 and RyR2 are required for Ca 2ϩ spark generation in these vascular myocytes, whereas RyR3 participates in global Ca 2ϩ responses induced by agonists and/or in the modulation of Ca 2ϩ spark frequency (6,32,33).…”
mentioning
confidence: 99%